Nurses’ Communicating with Patients in Peripheral and Border Areas in Indonesia: A Phenomenology Study - Petrus Kanisius Siga Tage; Herliana Monika Azi Djogo; Yulia M.K Letor; Maria Yoanita Bina; Rahmawati Rahmawati (Jurnal Keperawatan Padjadjaran, 2021)
Background: Communication is an important part of nursing care. However, Indonesian nurses still feel communication problems due to cultural and linguistic differences, especially in peripheral and border areas. Purpose: This study explores the communication experience of nurses when providing services to patients in three peripheries and two border areas of Indonesia. Methods: A phenomenological approach is used in this study. The purposive sampling technique was used to recruit 22 nurses in Indonesia’s periphery and border areas to be involved in the study. The data collection process was carried out from August to October 2021. Data were collected through interviews using a semistructured questionnaire, and verbatim transcripts of audio-recorded interviews were analyzed using thematic analysis. Results: This research resulted in four important themes, specifically: (1) difficulty in communicating, (2) emotional distress, (3) conflict and understanding, (4) lack of support for competency development. Conclusion: The findings of this study increase the scientific understanding of the communication barriers of nurses in the culturally diverse periphery and border areas. The barriers encountered can be used by nursing managers to construct ineffective nurse communication problem-solving interventions. The main emphasis on solving communication problems should include continuing education and training support so that nurses’ communication competence can be improved and applied in the service area based on the cultural and linguistic conditions of the patient.